2019
DOI: 10.3390/f11010049
|View full text |Cite
|
Sign up to set email alerts
|

Do Coffee Agroforestry Systems Always Improve Soil Carbon Stocks Deeper in the Soil?—A Case Study from Turrialba, Costa Rica

Abstract: Shaded perennial agroforestry systems (AFS) are regarded as desirable land-use practices that improve soil carbon sequestration. However, most studies assume a positive correlation between above ground and below ground carbon without considering the effect of past and current land management, textural variations (silt and clay percentage), and such other site-specific factors that have a major influence on the extent of soil C sequestration. We assessed SOC stock at various depths (0–10, 10–30, 30–60, and 60–1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 73 publications
0
10
0
3
Order By: Relevance
“…Los resultados de COS en la línea base fueron superiores a los que obtuvieron Balaba Tumwebaze y Byakagaba (2016) en sistemas agroforestales de café (54,01 t ha -1 ) en un clima semicálido húmedo de Uganda. Pero fueron inferiores con los datos que reportaron Zaro et al (2020), quienes encontraron que los suelos de algunos sistemas cafetaleros de Brasil almacenaron alrededor de 195,60 t ha -1 de C. También fueron inferiores a los resultados generados por Chatterjee et al (2020), en sistemas cafetaleros bajo sombra de Costa Rica que almacenaron hasta 146,6 t ha -1 de C. El COS que se encontró en este estudio diferió con los resultados obtenidos por Chatterjee et al (2020), Balaba Tumwebaze y Byakagaba (2016) y Zaro et al (2020), debido a que las tipologías de los suelos fueron diferentes en cada región, además de que la influencia del clima y el manejo agronómico del sistema fueron determinantes en las reservas de COS (Jansson & Hofmockel, 2020).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Los resultados de COS en la línea base fueron superiores a los que obtuvieron Balaba Tumwebaze y Byakagaba (2016) en sistemas agroforestales de café (54,01 t ha -1 ) en un clima semicálido húmedo de Uganda. Pero fueron inferiores con los datos que reportaron Zaro et al (2020), quienes encontraron que los suelos de algunos sistemas cafetaleros de Brasil almacenaron alrededor de 195,60 t ha -1 de C. También fueron inferiores a los resultados generados por Chatterjee et al (2020), en sistemas cafetaleros bajo sombra de Costa Rica que almacenaron hasta 146,6 t ha -1 de C. El COS que se encontró en este estudio diferió con los resultados obtenidos por Chatterjee et al (2020), Balaba Tumwebaze y Byakagaba (2016) y Zaro et al (2020), debido a que las tipologías de los suelos fueron diferentes en cada región, además de que la influencia del clima y el manejo agronómico del sistema fueron determinantes en las reservas de COS (Jansson & Hofmockel, 2020).…”
Section: Discussionunclassified
“…El incremento del COS en los tres diseños agroforestales a los veinte años, se debió a la rotación del cultivo de café y a la rotación de la cohorte de plátano a los diez años en D2 y D3. El suelo, tanto en la línea base como en la simulación a cincuenta años, representó el mayor reservorio de C en los diseños agroforestales de café evaluados, tal como se registró en diversas investigaciones (Chatterjee et al, 2020;Ehrenbergerová et al, 2016;Solis et al, 2020).…”
Section: Reservoriounclassified
“…This indicated that the carbon accumulation in the 0-10 cm layer depended on more litter contribution than only the carbon originating from the fine root turnover, as in natural systems of Brazilian biomes (OZÓRIO et al, 2019). The influence of the FRC stock in the 10-20 cm layer was high due to a decreasing carbon incorporation rate from the surface to the deeper layer (CHATTERJEE et al, 2020). AFS are known to have complex re-lations between species which results in a heterogeneous environment, especially in the soil-plant transition.…”
Section: Spatial Root Distribution Influencing Soil Organic Carbon Stockmentioning
confidence: 90%
“…In this work, fine roots were found in the surface layer and directly related to the higher concentration of organic matter and nutrients (WITSCHORECK; SCHUM-ACHER; CALDEIRA, 2003). Chatterjee et al (2020) also reported that the SOC stock in coffee AFS was increased only to a depth of 10 cm after 17 years of establishment due to shade-pruned Erytrina spp.…”
Section: Fine Root Contribution To the Soil Carbon Stock Of An Agrofomentioning
confidence: 93%
“…An increase of 1 g kg −1 (0.1%) of soil organic carbon increases the available water capacity of the soil by 6% (vol/vol). Increased capacity of available water, relevant for the survival of the dry season during the week [62,63].…”
Section: Role Of Agroforestry As Carbon Sink (Global Warming Impact M...mentioning
confidence: 99%